Fiber degrading enzymes increased monosaccharides release and fermentation in corn distillers dried grains with solubles and wheat middlings steeped without or with protease. Issue 3 (11th August 2020) - Rho, Youngji; Patterson, Rob; Joye, Iris; Martinez, Mario; Squires, E James; Kiarie, Elijah G
Abstract: Treating fibrous feed ingredients with exogenous feed enzymes may improve their utilization in monogastric animals. An in vitro study was conducted to determine the effects of steeping corn distillers dried grains with solubles (DDGS ) or wheat middlings (WM ) with exogenous feed enzymes. Four treatments were arranged as follows: 1) co-product steeped with water (CON ), 2) CON plus 0.5-g fiber degrading enzymes (FDE ), 3) CON plus 0.5-g protease (PRO ), and 4) CON plus 0.5-g FDE and 0.5 g PRO (FDEPRO ). The FDE contained about 62, 000, 37, 000, and 8, 000 U/g of xylanase, cellulase, and β-glucanase, respectively, whereas activities in PRO amounted to 2, 500, 000, 1, 300, 000, and 800, 000 U/g of acid, alkaline, and neutral proteases, respectively. Briefly, 50 g of DDGS or WM samples ( n = 8) were mixed with 500-mL water with or without enzymes and steeped for 0 to 72 h at 37 °C with continuous agitation. The pH, concentration of monosaccharides, and organic acids in the supernatant and apparent disappearance (AD ) of fiber in solids were measured at 0, 12, 24, 48, and 72 h. There was treatment and time interaction ( P < 0.005) on monosaccharides concentration. At 12 h, arabinose and glucose concentrations were similar ( P > 0.05) between FDE and FDEPRO but higher ( P = 0.002) than for CON in DDGS. For WM, FDE, and FDEPRO had higher ( P < 0.001) xylose concentration than CON and PRO, whereas glucose concentration was higher ( P < 0.001) for enzymes than CON at 12 h. However, FDEPRO had higher ( P < 0.001) xylose concentration than CON, whereas xylose concentration for FDE and PRO was intermediate at 24 h. There was an interaction ( P < 0.05) between treatment and time effect on lactic acid concentration in DDGS and WM ( P < 0.005), and acetic acid concentration in WM ( P < 0.001). In general, monosaccharide concentration was higher between 12 and 24 h and decreased after 48 h, whereas the pH decreased, and concentration of organic acids increased continuously over time ( P < 0.05). The AD of NDF and ADF in DDGS was greater ( P = 0.001) for FDE and FDEPRO than CON and PRO at 72 h. In WM, enzymes increased ( P = 0.007) AD of NDF relative to CON at 72 h. Nonetheless, greater ( P < 0.05) AD of fiber was observed between 48 and 72 h. In conclusion, although there were differences in responses among co-products, fiber degrading enzymes increased release of fermentable monosaccharides from co-products at 12 to 24 h of steeping and these effects were not extended with the addition of protease.